1973
DOI: 10.1063/1.1662889
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity in the piezoresistance coefficient of impact-loaded manganin

Abstract: The piezoresistance response of shock-loaded manganin wire embedded in C-7 epoxy insulation was experimentally determined over the stress range from 4 to 94 kbar. Manganin stress gauges of this configuration have been used extensively in previous shock wave studies. Interpretation of shock profiles below 50 kbar has been hampered, however, because the relationship between change in resistance and shock stress was not well established. The results of this work show the manganin piezoresistance coefficient to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The reason for using PMMA in the calibration studies was the fact that, owing to the epoxy backing of the gauge and the epoxy bonding used in the target assembly, one can consider the gauge to be embedded in a homogeneous material. This is so because epoxies and PMMA have close dynamic properties and, in particular, their Hugoniot curves are very close [9]. Millett et al [1] showed that an unfolding procedure developed for the grid gauge may also be used to interpret the MicroMeasurements 'T' gauges which are the subject of this paper.…”
Section: Introductionmentioning
confidence: 93%
“…The reason for using PMMA in the calibration studies was the fact that, owing to the epoxy backing of the gauge and the epoxy bonding used in the target assembly, one can consider the gauge to be embedded in a homogeneous material. This is so because epoxies and PMMA have close dynamic properties and, in particular, their Hugoniot curves are very close [9]. Millett et al [1] showed that an unfolding procedure developed for the grid gauge may also be used to interpret the MicroMeasurements 'T' gauges which are the subject of this paper.…”
Section: Introductionmentioning
confidence: 93%
“…Since then, several investigators have contributed to the understanding and calibration of the piezoresistance response of manganin under shock wave loading conditions, including Chen et al (1984), DeCarli (1976), Gupta and Gupta (1987), Kanel et al (1978), Lee (1973), and Postnov (1980).…”
Section: Methods For Measuring Stress Historiesmentioning
confidence: 99%